1998
DOI: 10.1074/jbc.273.15.8903
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Trapping of Tyrosyl Radicals Generated during Prostaglandin Endoperoxide Synthase Turnover

Abstract: Tyrosyl radicals have been detected during turnover of prostaglandin endoperoxide H synthase (PGHS), and they are speculated to participate in cyclooxygenase catalysis. Spectroscopic approaches to elucidate the identity of the radicals have not been definitive, so we have attempted to trap the radical(s) with nitric oxide (NO). NO quenched the EPR signal generated by reaction of purified ram seminal vesicle PGHS with arachidonic acid, suggesting that NO coupled with a tyrosyl radical to form inter alia nitroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 30 publications
5
77
0
5
Order By: Relevance
“…Thus, these findings indicate that NO induces the nitration of COX-2 in LPS-stimulated macrophages. As has been shown in cell-free systems by Gunther et al (9), it is likely that such nitration inhibits the catalytic activity of the enzyme, as those authors have reported (8,9). Whether COX-2 nitration decreases the stability of the enzyme and accounts for decreased COX-2 expression in NO-treated cells remains to be determined.…”
Section: No Inhibits Pge 2 Biosynthesis By Cox-1-deficient Cells or Bmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, these findings indicate that NO induces the nitration of COX-2 in LPS-stimulated macrophages. As has been shown in cell-free systems by Gunther et al (9), it is likely that such nitration inhibits the catalytic activity of the enzyme, as those authors have reported (8,9). Whether COX-2 nitration decreases the stability of the enzyme and accounts for decreased COX-2 expression in NO-treated cells remains to be determined.…”
Section: No Inhibits Pge 2 Biosynthesis By Cox-1-deficient Cells or Bmentioning
confidence: 81%
“…Tyr 385 contributes to enzyme activity; in addition, the tyrosyl radical species is involved in suicide inactivation (7). In cell-free systems, NO has been reported to trap the tyrosyl radical of the COXs, which leads to tyrosine iminoxyl radical formation and inactivation of the enzyme (8,9). The PG-biosynthetic pathway is initiated by activation of phospholipase A 2 (PLA 2 ), which are primarily responsible for agonistinduced arachidonic acid release from membrane phospholipids (10).…”
mentioning
confidence: 99%
“…The carboxylate moiety is anchored to Arg-120 and Tyr-355, and the fatty acid backbone extends upwards toward the top of the COX active site, with the 13-pro-S hydrogen of the substrate positioned close to Tyr-385 (32). The -end of arachidonate extends into the region we have termed the top channel, with carbons 17-20 lying above Ser-530.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ONOO Ϫ stimulates PGHS cyclooxygenase activity even in the presence of hydroperoxide-scavenging reaction systems, such as glutathioneϩGPx, 47,48 resulting in the proposal that ONOO Ϫ is a central mediator in tissue PGHS activation mechanisms.…”
Section: Reactive Nitrogen Species Stimulate Synthesis Of Pghs Metabomentioning
confidence: 99%